METHODOLOGY AND ALGORITHM FOR DECISION-MAKING IN CONDITIONS OF RISK AND UNCERTAINTY - Мормуль, Микола; Щитов, Дмитро; Щитов, Олександр (SWorldJournal, 2024)
The method of quantitative risk assessment by statistical method using absolute and relative indicators and qualitative risk assessment with the construction of an interval assessment of the effectiveness of strategies and determining the type of risk of